Activation in bed nucleus of the stria terminalis (BNST) corresponds to everyday helping. (June 2020) - Vekaria, Kruti M.; O'Connell, Katherine; Rhoads, Shawn A.; Brethel-Haurwitz, Kristin M.; Cardinale, Elise M.; Robertson, Emily L.; Walitt, Brian; VanMeter, John W.; Marsh, Abigail A.
Abstract: Everyday prosociality includes helping behaviors such as holding doors or giving directions that are spontaneous and low-cost and are performed frequently by the average person. Such behaviors promote a wide array of positive outcomes that include increased well-being, trust, and social capital, but the cognitive and neural mechanisms that support these behaviors are not yet well understood. Whereas costly altruistic responding to others' distress is associated with elevated reactivity in the amygdala, we hypothesized that everyday prosociality would be more closely associated with activation in the bed nucleus of the stria terminalis (BNST), a region of the extended amygdala known for its roles in maintaining vigilance for relevant socio-affective environmental cues and in supporting parental care. One previous study of the neural correlates of everyday prosociality highlighted a functional cluster identified as the septal area but which overlapped with established coordinates of BNST. We used an anatomical mask of BNST (Torrisi et al., 2015) to evaluate the association of BNST activation and daily helping in a sample of 25 adults recruited from the community as well as 23 adults who had engaged in acts of extraordinary altruism. Results found that activation in left BNST during an empathy task predicted everyday helping over a subsequent 14-day period in both samples. BNST activation most strongly predicted helping strangers and proactive helping. We conclude that beyond facilitating care for offspring, activation in BNST may provide a basis for the motivation to engage in a broad array of everyday helping behaviors.